Zeitenwende beim Automobil - Benzin und Diesel vor dem Aus? - Frondel, Manuel; Peistrup, Matthias (Deutscher Verkehrs-Verl., 2009)
In den vergangenen Jahrzehnten hat sich die Automobiltechnologie immer weiter entwickelt. Sicherheit, Effizienz, Umweltfreundlichkeit und Komfort konnten nachhaltig verbessert werden. Am grundlegenden Antriebskonzept und an den zum Einsatz kommenden Kraftstoffen hat sich allerdings nicht viel geändert. Auch heute werden nahezu 100 % aller in Deutschland zugelassenen Kraftfahrzeuge durch einen Verbrennungsmotor angetrieben, der einen aus Erdöl gewonnenen Kraftstoff nutzt.

Discussions of alternative propulsion technologies for motor cars have, without any really new impulses, intensified notably over the last decade and involved the public at large. Almost all the well-known car manufacturers are in the process of developing hybrid and electrical drives or are carrying out research into new fuel cells. It is, however, too early to talk about profound technological and ecological changes for motor cars. The future role of new motor drives cannot be ascertained as yet since it is so closely associated with technological development, political regulations, appropriate supply infrastructure and customers' concern about a car's handling characteristics and sales price. The classic combustion engine has not yet reached its full potential and is likely to remain the principal drive medium term, since alternative concepts continue to be faced with unresolved economic and technological problems, while currently registered cars are likely to remain in use within the next fifteen years Instead of talking about a revolution, the focus is more on motorization that better meets individuals' future mobility requirements, with emphasis on electro mobility for short haul and city traffic and efficient combustion engine-based motor drives for longer journeys.
A new beginning for the motor car - are petrol and diesel fuel on their way out?
Keywords: Verkehr; Kraftfahrzeug; Verbrennungsmotor; Antrieb; Mobilität; Neue Technologie; Verkehrsinfrastruktur; Umweltbelastung; Kohlendioxid; Prognose; Nachhaltigkeit; Kraftstoff; Technische Entwicklung; Elektrofahrzeug; Treibhausgas